Human-robot collaboration in surgery at the nexus of knowledge, agency, and ownership - Merdin-Uygur, Ezgi; Ozturkcan, Selcen; Ozbilgin, Mustafa F.; Yilmaz, Faruk; Ince, Ozgur (Nature Portfolio, 2025)
Human-robot collaboration is transforming healthcare, particularly in surgical environments. Robotic surgery systems, embodied by advanced AI, are pivotal in augmenting human expertise across specialties such as gynecology and laparoscopic surgery. However, critical gaps remain in understanding how knowledge, agency, and ownership shape these collaborations. We address these gaps through semi-structured interviews with eleven healthcare professionals from diverse surgical roles. Our findings reveal that while robotic systems enhance precision and efficiency, they also generate tensions related to professional autonomy, control, and responsibility. Participants expressed ambivalent views, simultaneously demonstrating trust in the technology and strategic disengagement to preserve human authority. Concepts such as avatarization, the perception of robots as extensions of the self, and strategic ignorance emerged as key mechanisms through which professionals manage this evolving relationship. These dynamics point to the need for rethinking human-robot roles as fluid and co-constructed rather than fixed or hierarchical. We also emphasize the possible use of robotic systems to promote inclusivity and accessibility in healthcare while identifying structural barriers such as high costs, dependence on proprietary technology, and uneven organizational readiness. Our research enhances theoretical frameworks on human-robot interaction, providing practical and conceptual insights for the creation of equitable, sustainable, and context-sensitive robotic healthcare systems.
Keywords: Robotic surgery; Healthcare robots; Human-robot relationship; Knowledge; Agency; Ownership; Professional ignorance